On the preferences of CoCo bond buyers and sellers: a logistic regression analysis - Guglielmo Maria Caporale; Woo-Young Kang (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper estimates the preference scores of CoCo bond buyers and sellers by running logistic regressions taking into account both bond and issuing bank's characteristics, and also considers the role of country-specific CoCo bond market competitiveness. Buyers are found to be characterised by stronger preference responses to CoCo bond coupons and credit ratings, while sellers are more sensitive to CoCo bond issue size and financial characteristics including return on common equity, price-to-book ratio and total regulatory capital to risk-weighted asset ratio. Further, sizeable responses to CoCo bond and issuing bank's characteristics are found in most European countries, Brazil, Mexico and China, the strongest responses being estimated in the case of the UK and China.
Keywords: C25; C39; F39; G11; G21; G24; G28; 330; CoCo bonds; buyers and sellers; preference scores; logistic regressions